Bechem Technologies Sdn. Bhd / Muhammad Iqbal Mohamed Mahathir - Mohamed Mahathir, Muhammad Iqbal (Faculty Of Chemical Engineering, 2021)
I have gained a lot of knowledge in water treatment including the process flow, equipment used and chemical test. As a trainee at Bechem, I able to improve my time management skills because this company taught to be punctual in everything. My supervisor also helped me a lot to complete my internship such as performing jar test, writing IECS report and many more. I hope that working at Bechem will give me experience so that I can continue working at any industry. For recommendation, I think Bechem should involve the trainee more in the company's project to give more experience to the trainee. Bechem also should improve their working system because sometimes I had nothing to do in the office. So, I think Bechem should give more task to trainee to help them improve their employability skills and become a successful engineer.